A fluorinated SEI layer induced by a fire-retardant gel polymer electrolyte boosting lateral dendrite growth. Issue 41 (4th October 2022) - Wen, Ziyue; Zhao, Zhikun; Zhang, Ting; Wang, Yuanshen; Zhang, Jinxiang; Sun, Zhaoyang; Li, Li; Li, Yuejiao; Wu, Feng; Chen, Renjie
Abstract : A flame-retardant electrolyte fabricated by the in situ polymerization method facilitates lateral Li dendrite growth induced by a LiF-rich SEI layer. Abstract : Gel polymer electrolytes (GPEs) have attracted widespread attention for Li metal batteries (LMBs) due to their excellent processability and low cost. However, they are generally flammable and incompatible with the electrode, posing serious safety hazards. Herein, a high-safe electrolyte was successfully designed and fabricated by in situ introduction of a flame-retardant phosphate-based electrolyte into a robust polymer matrix. The facile in situ polymerization method adopted in this work effectively improves the contact between the electrolyte/electrode interface. Interestingly, the controlled formation and lateral growth of Li dendrites in deposition process was regulated by the fluorinated solid-electrolyte interphase (SEI) layer, enhancing the stability and safety of LMBs. Particularly, the components and distribution of the SEI were further studied by Fourier transform infrared (FTIR), FTIR-mapping and X-ray photoelectron spectroscopy (XPS) analysis to explore the mechanism of lateral dendrite growth. As expected, the Li metal is well protected, and the Li|Li symmetric batteries were stabilized for 2100 h under changing temperature conditions. This work provides fundamental insights into a facile method for preparing GPEs with potential applicability for next-generation flexible and safe energy-storage devices.